A new dark-saddled species of Hypostomus (Siluriformes: Loricariidae) from the upper rio Paraguay basin - Zawadzki,Cláudio Henrique (2010)
A new Hypostomus species is described from the rio Cuiabá, upper rio Paraguay basin, Mato Grosso State, Brazil. The new species is distinguished from all other Hypostomus species, with exception of young specimens of H. latifrons, by the presence of a wide dark transverse bars on laterals of body and fins; and conspicuous dark vermiculations on abdominal region. From H. latifrons it differs by having just one pre-dorsal plate surrounding supraoccipital bone and by the maintenance of the dark saddles in adults. Added to the other fish species recently described from the upper rio Paraguay basin, this work helps to highlight that the region still functions as a potential source of new species.